4G over 3G Mobile Broadband Speed Improvements on Smartphones from End Users Perspective - Ali, Mubashir (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Mobile & wireless communication has been one of the hottest thing and developing extremely fast in present times, thanks to the advances of technology in all the fields of mobile and wireless communications. It has not been a long time that 4th generation of mobile networks i.e. 4G, is introduced. Since then, there has been hype all around regarding the numerous advantages of 4G and that, it is better than 3G. This paper will discuss the uses of mobile broadband on smartphones; compare the data speeds of 3G and 4G and how the speed improvement of 4G over 3G makes not much of a difference to an end user using internet on smart phones / mobile phones.